2021
DOI: 10.3126/md.v24i2.50041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Service Quality on Customer Satisfaction and Loyalty

Abstract: This paper has analyzed the impact of service quality on customer satisfaction and customer loyalty of NTC. For this purpose, this paper has used five dimensions of service quality - tangibles, reliability, assurance, empathy and responsiveness, as proposed by Parasuraman, Berry and Zeithaml (1991). The required data for the study has been collected using a structured questionnaire from the customer of NTC of Surkhet Valley. Using the multiple regression analysis, this paper finds the significant positive impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(37 reference statements)
2
2
0
3
Order By: Relevance
“…In addition, (Syafarudin, 2021) found that the quality of the product affects consumer satisfaction. Similarly, research (Sambo et al, 2022) also found that product quality positively and significantly influences customer satisfaction. Aspects of brand diversity and varied products also have high satisfaction, with an average level of customer agreement of 4.13.…”
Section: Page251mentioning
confidence: 81%
“…In addition, (Syafarudin, 2021) found that the quality of the product affects consumer satisfaction. Similarly, research (Sambo et al, 2022) also found that product quality positively and significantly influences customer satisfaction. Aspects of brand diversity and varied products also have high satisfaction, with an average level of customer agreement of 4.13.…”
Section: Page251mentioning
confidence: 81%
“…Furthermore, it identifies "Customer Satisfaction" as essential to keeping customers loyal to the organization's services. As a result, it concludes that service quality is the most crucial factor in keeping customers satisfied and loyal (Shrestha, 2021).…”
Section: Reliabilitymentioning
confidence: 94%
“…Kualitas sistem berkaitan dengan aspek teknis platform ecommerce, termasuk keandalan, daya tanggap, dan keramahan penggunanya. Kualitas layanan, di sisi lain, berkaitan dengan kaliber layanan pelanggan yang ditawarkan oleh platform e-commerce, yang mencakup daya tanggap, empati, dan jaminan (Shrestha, 2021). Kualitas sistem sangat penting dalam membentuk kepuasan konsumen, dan pengaruh kualitas sistem dan kualitas website berdampak langsung dan positif terhadap kepuasan pelanggan.…”
Section: System Quality Berpengaruh Terhadap Customer Satisfactionunclassified
“…Temuan penelitian menunjukkan bahwa keandalan dan empati adalah faktor yang paling berpengaruh dalam menentukan kepuasan pelanggan, dengan responsivitas memiliki dampak yang relatif lebih rendah. Kualitas layanan adalah faktor paling penting dalam memastikan kepuasan pelanggan (Shrestha, 2021;Thamnopoulos et al, 2012;Zygiaris et al, 2022). Kualitas layanan memiliki pengaruh positif terhadap kepuasan pelanggan, dan pelanggan yang puas lebih mungkin untuk terus melakukan bisnis dengan perusahaan di masa depan.…”
Section: System Quality Berpengaruh Terhadap Customer Satisfactionunclassified
See 1 more Smart Citation